A comparison of the potency of a novel bispyridinium oxime K203 and currently available oximes (obidoxime, HI-6) to counteract the acute neurotoxicity of sarin in rats - Kassa, Jiri; Misik, Jan; Karasova, Jana Zdarova (Basic & clinical pharmacology & toxicology, 2012)
The neuroprotective effects of a newly developed oxime K203 and currently available oximes (obidoxime, HI-6) in combination with atropine in rats poisoned with sarin were studied. The sarin-induced neurotoxicity was monitored using a functional observatory battery at 2 hr after sarin challenge. The results indicate that the potency of a novel bispyridinium oxime K203 to counteract sarin-induced neurotoxicity is relatively low and roughly corresponds to the neuroprotective efficacy of obidoxime. Among tested oximes, the oxime HI-6 seems to be significanlty more efficacious to counteract acute neurotoxicity of sarin than commonly used obidoxime and a newly developed oxime K203. Thus, the oxime K203 does not provide any beneficial effect for the antidotal treatment of acute poisoning with sarin in comparison with the oxime HI-6 that should be considered to be the best oxime for antidotal treatment of acute sarin poisonings.
Keywords: pyridinové sloučeniny; oximy; Pyridinium Compounds; antidota; Oximes; LD50; chemické bojové látky; krysa rodu Rattus; zvířata; antagonisté muskarinových receptorů; neurony; Neurotoxicity Syndromes; Muscarinic Antagonists; potkani Wistar; cholinesterasové inhibitory; sarin; Rats, Wistar; Male; Atropine; atropin; reaktivátory cholinesterasy; Czech Republic; Lethal Dose 50; Neurons; Psychomotor Performance; Cholinesterase Reactivators; autonomní nervový systém; Sarin; Rats; neurotoxické syndromy; Animals; Chemical Warfare Agents; Obidoxime Chloride; Autonomic Nervous System; Česká republika; mužské pohlaví; Cholinesterase Inhibitors; kombinovaná farmakoterapie; obidoxim chlorid; psychomotorický výkon; Drug Therapy, Combination; Antidotes